Inventory control by using Fuzzy set theory An Applied Research at the Baghdad Soft Drinks Company - خلف, وقاص سعد; جاسم, عبد الله باسم (Journal of Economics and Administrative Sciences, 2017)
The production companies in the Iraqi industry environment facing many of the problems related to the management of inventory and control In particular in determining the quantities inventory that should be hold it. Because these companies  adoption on personal experience and some simple mathematical methods which lead to the identification of inappropriate quantities of inventory.       This research aims to identify the economic quantity of production and purchase for the Pepsi can 330ml and essential components in Baghdad soft drinks Company in an environment dominated by cases of non ensure and High fluctuating as a result of fluctuating demand volumes and costs associated with inventory, and has been using the fuzzy time series method to dispose of uncertainty and fluctuation accompanying demand for finished product , and using the fuzzy inference system (If-Then Rules) to remove the cases of uncertainty associated with the holding inventory cost for the finished product and essential components.      After removing the fuzzy of demand and holding inventory cost Parameters, been used the production model without Shortage to determine the economic production quantity for the Pepsi can 330 ml, and the purchase model without Shortage to determine the economic order quantity for the product components. The statistical programs (Matlab, Win Qsb.v2) were used for mathematical and statistical analyzes.